The extension of Willmore's method into 4-space - Duldul, Bahar Uyar; Duldul, Mustafa (UNIV OSIJEK, DEPT MATHEMATICS, 2012)
We present a new method for finding the Frenet vectors and the curvatures of the transversal intersection curve of three implicit hypersurfaces by extending the method of Willmore into four-dimensional Euclidean space.
Keywords: implicit hypersurface; implicit curve; transversal intersection; curvatures; DIFFERENTIAL GEOMETRY; INTERSECTION CURVES; SURFACES; Mathematics